Primary Occipital Ewing’s Sarcoma with Subsequent Spinal Seeding - Ali Alqahtani; Roaa Amer; Eman Bakhsh (Case Reports in Pediatrics)
Ewing’s sarcoma is a primary bone cancer that mainly affects the long bones. This malignancy is particularly common in pediatric patients. Primary cranial involvement accounts for 1% of cases, with occipital involvement considered extremely rare. In this case study, primary occipital Ewing’s sarcoma with a posterior fossa mass and subsequent relapse resulting in spinal seeding is reported. A 3-year-old patient presented with a 1-year history of left-sided headaches, localized over the occipital bone with progressive torticollis. Computed tomography (CT) imaging showed a mass in the left posterior fossa compressing the brainstem. The patient then underwent surgical excision followed by adjuvant chemoradiation therapy. Two years later, the patient presented with severe lower back pain and urinary incontinence. Whole-spine magnetic resonance imaging (MRI) showed cerebrospinal fluid (CSF) seeding from the L5 to the S4 vertebrae. Primary cranial Ewing’s sarcoma is considered in the differential diagnosis of children with extra-axial posterior fossa mass associated with destructive permeative bone lesions. Although primary cranial Ewing’s sarcoma typically has good prognosis, our patient developed metastasis in the lower spine. Therefore, with CNS Ewing’s sarcoma, screening of the entire neural axis should be taken into consideration for early detection of CSF seeding metastasis in order to decrease the associated morbidity and mortality.